The relationship of flat foot with static balance and dynamic balance - Rizqillah, Indah Prima; Sudaryanto, Wahyu Tri (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2025)
Background: The foot is a part of the body that function is to support the body weight and to maintain balance while standing, but the foot also has many problems, one of which is flat foot, a type of flat foot caused by the flattening of the bone's curvature, which is the lack of arches on the soles of the feet. The weakness of the plantaris ligament, posterior and anterior tibial tendons, and intrinsic muscles, which maintain the medial longitudinal arch, are the cause of this foot deformity that can have an impact on health. Flat feet that occur in the community are often ignored and considered to be normal. Poor foot conditions will affect the fulcrum, one of the foot conditions that can affect the fulcrum is flat foot. When a child has the flat foot, the resulting fulcrum is also going to be bad, it will affect the balance. Purpose: To ascertain how flat foot relates to both static and dynamic balance. Method: A cross-sectional approach, specifically focusing on observational study. The study took place from June 2024, in MI Muhmmadiyah Gonilan, Surakarta. The independent variable was flat foot the dependent variables is a static balance and dynamic balance. Using purposive sampling and the Slovin formula, 108 participants were selected. Univariate statistical analysis was conducted, bivariate data analysis using Spearman rank test. Results: The correlation coefficient value of 0.645 falls into the strong relationship category, while the correlation coefficient value of 0.207 is classified as a weak relationship. Additionally, the significance value of <0.05 indicates a statistically significant relationship between flat foot and both static and dynamic balance. Conclusion: The analysis showed that while there was a correlation between flat feet and both types of balance, the degree of association was different. Flat feet had a very weak relationship with dynamic balance, while its relationship with static balance was stronger and more significant. Thus, it can be said that flat feet have more influence on static balance than dynamic balance.